Step
*
1
of Lemma
finite-double-negation-shift
1. [A] : ℙ
2. [B] : ℕ ⟶ ℙ
3. n : ℕ@i
4. ∀n1:ℕn. ((∀i:ℕn1. (((B i)
⇒ A)
⇒ A))
⇒ ((∀i:ℕn1. (B i))
⇒ A)
⇒ A)@i
5. ∀i:ℕn. (((B i)
⇒ A)
⇒ A)@i
6. (∀i:ℕn. (B i))
⇒ A@i
7. n = 0 ∈ ℤ
⊢ A
BY
{ (D (-2) THEN Auto)⋅ }
Latex:
Latex:
1. [A] : \mBbbP{}
2. [B] : \mBbbN{} {}\mrightarrow{} \mBbbP{}
3. n : \mBbbN{}@i
4. \mforall{}n1:\mBbbN{}n. ((\mforall{}i:\mBbbN{}n1. (((B i) {}\mRightarrow{} A) {}\mRightarrow{} A)) {}\mRightarrow{} ((\mforall{}i:\mBbbN{}n1. (B i)) {}\mRightarrow{} A) {}\mRightarrow{} A)@i
5. \mforall{}i:\mBbbN{}n. (((B i) {}\mRightarrow{} A) {}\mRightarrow{} A)@i
6. (\mforall{}i:\mBbbN{}n. (B i)) {}\mRightarrow{} A@i
7. n = 0
\mvdash{} A
By
Latex:
(D (-2) THEN Auto)\mcdot{}
Home
Index